2018
DOI: 10.1176/appi.neuropsych.17060123
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia Under-Diagnosis in the General Hospital

Abstract: Catatonia is under-diagnosed in psychiatric settings. No studies have explored the under-diagnosis of catatonia in general hospitals. The authors conducted a retrospective chart review using DSM-5 criteria to diagnose catatonia in medical inpatients between 2011 and 2013. Of 133 case subjects meeting DSM-5 criteria for catatonia retrospectively, 79 had never been diagnosed and 54 had a documented diagnosis. Multiple logistic regression revealed that psychiatry consultation significantly decreased the odds of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 37 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…The most common catatonic signs and symptoms in this study were mutism, posturing, and withdrawal, all of which were present in all 18 patients. This finding is in keeping with previous research [3,31]. In our study, most of the patients were younger than 30 years old and male.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The most common catatonic signs and symptoms in this study were mutism, posturing, and withdrawal, all of which were present in all 18 patients. This finding is in keeping with previous research [3,31]. In our study, most of the patients were younger than 30 years old and male.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, there is no recorded catatonia sign of excitement, echopraxia/echolalia, stereotypy, mannerisms, verbigeration, stereotypy, impulsivity, grasp reflex, perseveration, and combativeness. It has also been argued that in comparison to classic psychiatric literature, modern research on catatonia has focused more on motor rather than verbal signs of catatonia, including echolalia and verbigeration [3,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of catatonia differs in different medical settings ranging from 5%-18% on inpatient psychiatric units, 12% in drug-naive patients with first-episode psychosis, 3.3 on a neurology/neuropsychiatric tertiary care inpatient units, 1.6% to 1.8% on psychiatry consultation-liaison services, 8.9% in elderly patients and 3.8% on intensive care units. 5 It has been reported that catatonia carries a high risk of morbidity and mortality, partly due to failure of timely recognition and initiation of appropriate treatment. 6 Catatonia appears to be a risk factor for developing neuroleptic malignant syndrome, which has a mortality rate of approximately 10% and may be clinically difficult to distinguish from malignant catatonia.…”
Section: Introductionmentioning
confidence: 99%